Moderation Of Leadership Style On The Influence Of Compensation And Work Culture On Occupational Therapist Loyalty - Dwi Bimantoro; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study used a quantitative descriptive approach. In this quantitative descriptive study, the author focuses research on moderating leadership styles on the influence of compensation and work culture on occupational therapist loyalty. This research is located in all child growth and development clinics in Bekasi City. In conducting this study, the time needed was for 6 months starting from observation to making data results and conclusions of population research in this study were Occupational Therapists who work in Bekasi City, totaling 61 people, the samples taken in this study were 61 Occupational Therapists who works at child growth and development clinics in Bekasi City. The data that has been obtained is analyzed using the SEM-PLS analysis tool using the help of SMARTPLS software. After an in-depth discussion of the data obtained, the resulting conclusions are Compensation, Work Culture and Leadership Style directly have a significant effect on Occupational Loyalty. For the Moderation Variable, it can be concluded that Leadership Style in moderating has no influence between compensation and loyalty of the Occupational Therapist. Similarly, moderating leadership style also has no influence between work culture and loyalty